Uruguay : Maintaining Social Equity in a Changing Economy - World Bank (Washington, DC, 2013)
This report focuses on understanding key issues related to poverty, vulnerability and social policy in the context of a changing Uruguayan economy. Because the country is highly urbanized (90 percent), and data on rural areas are scant, most of the analysis in this study focuses on urban areas. Chapter 1 presents a profile of poverty and its trends in the nineties using household survey data. Chapter 2 looks at changes in the structure of the economy and the link with problems of unemployment, underemployment, and labor insecurity over the past decade. Chapter 3 focuses on the specific issues of marginalization and vulnerability based on a qualitative study carried out in poor urban neighborhoods surrounding Montevideo. Chapter 4 analyzes Government social expenditures, with particular emphasis on how effective these expenditures are at reaching the poor and meeting the needs of vulnerable groups. Background papers with detailed analysis are also available under separate cover. Policy recommendations are included in this summary.